Clinical-Morphological and Immunological Diagnostic Aspects of Neonatal Pneumonia in Early Childhood - Каdirov Кomiljon Zakirdjanovich; Abduvalieva Chulpanoy Muhammadjonovna (Genius Journals, 2024)
Neonatal pneumonia (NP) is one of the most severe manifestations of perinatal pathology. In accordance with official statistics, the incidence of pneumonia is about 1% among full-term and about 10% among premature babies, and reaches 40% in newborns in the intensive care unit with various types of respiratory pathology.In recent years, factors of innate immunity, in particular, recognizing receptors, have been actively studied. Toll-like receptors (TLRs) are of great importance in pathogen recognition. The expression profile of receptor and effector molecules of innate immunity at the level of mucous membranes may indicate the functional activity of innate mucosal immunity. So far, the issues about the role of innate immunity factors in the development of neonatal pneumonia remain poorly understood
Keywords: neonatal pneumonia; children; immunity; clinical and morphological studies